Parental Attitudes and Behaviors Towards the Prevention of Sexual Violence against Children in a Health Perspective - Nurul Aini; Ika Rizki Anggraini; Aini Alifatin (Malahayati Nursing Journal, 2022)
ABSTRACT The role of parents in mentoring the child's growth and development phase is very important. How parents provide sexual education to children has not been widely illustrated, this reality is very concerning, considering that the news exposed today contains a lot about the increase in the level of violence that occurs in children, especially sexual violence. The purpose of this study is to identify parents' attitudes and behaviors towards the prevention of sexual violence in children, especially from a health perspective. This research method uses observational analysis with a cross-sectional study approach. The population and sample were parents who had school-age children (aged 6-12 years) in East Java. The data were taken using a questionnaire containing questions about attitudes and behaviors in terms of the prevention of sexual violence in children carried out by parents and will be analyzed with a chi square test. The results of this study showed that good parental attitudes have a relationship with parental behavior towards the prevention of sexual violence in children in a health perspective with a category of good behavior of 20 respondents, enough 58 respondents, and less 3 respondents. Meanwhile, parents' attitudes are quite good in relationto parental behavior towards the prevention of sexual violence in children in a health perspective with a good category of 6 respondents, enough 43 respondents, and less than 10 respondents. The conclusions of this study show that parents' attitudes in educating and preventing sexual violence against children are influenced by several factors such as education, level of knowledge and parents' habits. Keywords: Attitudes, Behaviors, Parents, Sexual Violence, Children